Design and development of an assistive hand orthosis for hand and finger motor training - Wong, Chi Heim (2024)
There are currently lack of assistive devices connected to internet-of-things (IoT), which enables precise real-time, and remote control and monitoring of the patients during finger fine motor rehabilitation. This study aimed to enhance existing hand therapy tool by developing a portable, cost-effective (RM 383.29), lightweight (500 g) and remotely controllable active assistive hand orthosis (AHO) to enhance fine motor training of fingers. The AHO was designed to assist in actuating flexion-extension movements of all 4 fingers and thumb in the metacarpophalangeal (MCP) joint, and grasping movement. The mechanical frame was designed using computer-aided software (CAD) and additive manufactured with polylactic acid (PLA) filaments. The functional components include inertial measurement units (IMUs) that measure the range of motion of the index finger and thumb; servo motors that enable precise linear actuation in performing specific finger and thumb movements; a microcontroller as the control system; and a simple Internet of Things (IoT) user interface that aid the therapists in monitoring rehabilitation progress of individual patient during home-based rehabilitation, as well as controlling the exoskeleton remotely. This AHO can perform 4 fingers flexion/extension and thumb flexion/extension on subjects with various hand sizes (15.5 cm to 18 cm) consistently with a low standard deviation (SD < 10), and it can aid on users’ grip strength with a percentage increase of 16.86% and 14.09% of index finger and thumb respectively. Experimental outcomes showed that the AHO was able to acquire, display and store relevant data accurately when assisting participants to perform repetitive flexion/extension movement and practice grasping on objects of various shapes and sizes. This proof of concept demonstrated the AHO can assist and has the potential to improve the effectiveness of fine motor trainings in hand and finger rehabilitation, besides providing more convenience to the users and therapists.